Experts vs. discounters: Consumer free riding and experts withholding advice in markets for credence goods - Uwe Dulleck; Rudolf Kerschbamer (University of Innsbruck, Department of Public Finance, 2007)
This paper studies the incentives for credence goods experts to invest effort in diagnosis if effort is both costly and unobservable, and if they face competition by discounters who are not able to perform a diagnosis. The unobservability of diagnosis effort and the credence characteristic of the good induces experts to choose incentive compatible tariff structures. This makes them vulnerable to competition by discounters. We explore the conditions under which honestly diagnosing experts survive competition by discounters; we identify situations in which experts misdiagnose consumers in order to prevent them from free riding on experts' advice; and we discuss policy options to solve the free-rider problem.
Keywords: L15; D82; D40; 330; experts; discounters; credence goods; advice; free riding; Preiswettbewerb; Facheinzelhandel; Discounter; Wettbewerbstheorie